Small and large fiber neuropathy in those with type 1 and type 2 diabetes: a 5‐year follow‐up study. Issue 1 (March 2016) - Løseth, Sissel; Stålberg, Erik V.; Lindal, Sigurd; Olsen, Edel; Jorde, Rolf; Mellgren, Svein I.
Abstract: The purpose of this study was to evaluate progression of diabetic polyneuropathy and differences in the spectrum and evolution of large‐ and small‐fiber involvement in patients with diabetes type 1 and 2 over 5 years. Fifty‐nine patients (35 type 1 and 24 type 2) were included. Nerve conduction studies (NCS), quantitative sensory testing, skin biopsy for quantification of intraepidermal nerve fiber density (IENFD), symptom scoring and clinical evaluations were performed. Z‐scores were calculated to adjust for the physiologic effects of age and height/gender. Neuropathic symptoms were not significantly more frequent in type 2 than in type 1 diabetic patients at follow‐up (54% vs. 37%). The overall mean NCS Z‐score remained within the normal range, but there was a small significant decline after 5 years in both groups: type 1 (p = 0.004) and type 2 (p = 0.02). Mean IENFD Z‐scores changed from normal to abnormal in both groups, but only significantly in those with type 2 diabetes (reduction from 7.9 ± 4.8 to 4.3 ± 2.8 fibers/mm, p = 0.006). Cold perception threshold became more abnormal only in those with type 2 diabetes (p = 0.049). There was a minimal progression of large fiber neuropathy in both groups. Reduction of small fibers predominated and progressed more rapidly in those with type 2 diabetes.